The perspectives of port integration into the global supply chains : the case of north Adriatic ports - Host, Alen (Array, 2018)
Globalization, offshoring and the notable growth of containerization have changed the maritime transport and logistics chains. Ports became integral part of complex supply chains and serve as a logistics centres, add value, link flows and influence the supply chain patterns and processes. The port competitiveness is determined by its in-house strengths such as efficient freight handling and hinterland connections and by its position and links in the global supply chains. The aim of this paper is to investigate the importance of port integration in the supply chains overall and to analyse how North Adriatic Ports are integrated into the supply chains. The analysis is based on the sample of 939 firms aggregated by ports regions and classes level within Section H (Nace Rev.2). The assumption is that if the business cycle of all firms (classes) included in the port supply chain is correlated, it can indicate that the port is integrated in the supply chain. The results of our analysis are ambiguous, where the correlation is rather negative than positive. This paper provides the conceptual framework and outline the significance of this investigation for port operators, shipping lines, forwarders and other stakeholders.